ANALISIS JALUR FAKTOR YANG MEMPENGARUHI MOTIVASI MENABUNG SISWA SEKOLAH DASAR - Wardani, Dian Kusuma (Exact Papers in Compilation (EPiC), 2019)
Path analysis was developed by Sewall Wright in 1934 which aims to explain the direct and indirect effects of a set causal variable (exogenous variables) on a set of variables (endogenous variables). Primary data used in this study. The total population is 70538 Public Elementary School students in Jombang district. The sampling technique used was simple random sampling, and 270 samples were taken from the population. The purpose of this study was to determine the structural relationship between exogenous variables (parent motivation, teacher motivation) on endogenous variables (students' understanding of money and saving and motivation to save). The results showed that the variable Y2 (motivation of students saving) had direct and indirect influenced on variables X1 (parent) and X2 (teacher).